Acceptance and experience of digital dental technology, burnout, job satisfaction, and turnover intention for Taiwanese dental technicians - Tang-Yun Teng; Ju-Hui Wu; Chen-Yi Lee (BMC, 2022)
Abstract Background Digital dental technology (DDT) has progressed and been introduced to Taiwan in the recent years, gradually changing the industry ecology. Many studies have demonstrated that DDT is more accurate and faster than conventional dental technology. However, there is a paucity of research exploring dental technicians' perspectives on digital dental techniques, and their burnout, job satisfaction, and turnover intention. Methods This cross-sectional survey with convenience sampling was conducted at the conference venue of the Taiwan Association of Dental Technology to investigate the perspectives of dental technicians. We used the snowballing method in this study; two sampling methods were adopted, a convenience sampling of dental technicians to complete a survey, followed by asking the survey participants of the convenience sample to invite their colleagues to participate in the online survey. The survey questionnaire included questions on demographics, work-related information, acceptance and experiences of dental technicians toward DDT, occupational burnout, job satisfaction, and turnover intention. Regression models were used to determine the predictors of job satisfaction and determinants of turnover intention. Results In total, 341 valid questionnaires were obtained. Overall, the participants reported long working hours (95.5%), positive score on the DDT acceptance scale, moderate job satisfaction, higher personal burnout, and work burnout, along with lower over-commitment. Among them, 32.9% and 28.2% reported the intention to leave their organization and profession, respectively. The stepwise multiple regression model revealed that higher work burnout decreased job satisfaction, while higher DDT acceptance and position as employer increased job satisfaction. The binary logistic regression models revealed that geographical area of workplace, work burnout, and job satisfaction were significant predictors of turnover intentions. Conclusions Many Taiwanese dental technicians reported turnover intentions and higher burnout. With the trend of digitalization in the dental industry, even though most dental technicians had a positive outlook toward DDT, its influence on job satisfaction appears limited. Retaining good and professional talents required of a dental technician is crucial, especially as Taiwan's dental care becomes increasingly specialized. Strategies for improving the work environment and occupational health of dental technicians should thus be the focus of future studies.